The Organized Corruption through Influential Groups’ Networks: The Cases of a Teachers’ Saving Cooperative and a Futsal Field Construction Project - promgird, pornamarin; sririn, warunya; loiwirat, thiraphat; luangkaew, pherm (King Prajadhipok’s Institute Journal, 2020)
This article aims to investigate the types and behavioral characteristics of organized corruption among influential groups consisting of senior government officials, politicians, and business people. This qualitative study was conducted by collecting two types of data. Primary data were collected by using in-depth personal interview and focus group discussions in the Secondary Educational Service Areas 24, 25, and 26. Secondary data were collected by examining court judgments, documents from government anti-corruption agencies, and information from some press agencies. The data were analyzed using descriptive analysis. The study found that both teachers’ saving cooperation and futsal field construction both involved some behavioral characteristics of cooperative corruption and were related with influential group-networks, finally leading to organized corruption.